2023
DOI: 10.1007/s00431-023-05034-9
|View full text |Cite
|
Sign up to set email alerts
|

Only one beer can be mortal: a case report of two sisters with cardiac arrest due to a homozygous mutation in PPA2 gene

Abstract: We report the long way to the correct diagnosis in two teenage sisters who developed a cardiac arrest after consuming minimal amounts of alcohol. The older girl dramatically survived two cardiac arrests at the age of 14 and 15 years. She underwent an extensive examination that revealed isolated cardiac abnormalities including fibrosis, dilated cardiomyopathy and inflammation. The younger girl also had a cardiac arrest at the age of 15 and died suddenly after consuming 1–2 beers, 3 years after her sister´s firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Max LOD = 2.8 (estimated) 87 LV traits PPA2 Inorganic pyrophosphatase DCM/SCD 7 (refs. 7 , 8 , 89 93 ) 32 53 Missense Exome (21 trio, 3 proband). Panel (8 trio) PPP1R13L NF-κB and p53 inhibitor DCM 6 (refs.…”
Section: Resultsmentioning
confidence: 99%
“…Max LOD = 2.8 (estimated) 87 LV traits PPA2 Inorganic pyrophosphatase DCM/SCD 7 (refs. 7 , 8 , 89 93 ) 32 53 Missense Exome (21 trio, 3 proband). Panel (8 trio) PPP1R13L NF-κB and p53 inhibitor DCM 6 (refs.…”
Section: Resultsmentioning
confidence: 99%
“…The paternally inherited variant, PPA2 c.683 C>T (p.P228L), has been described in 14 individuals with PPA2 deficiency and has an estimated population frequency of 0.0043% (gnomAD: 66/152018, no homozygotes). 2 , 7 , 8 , 9 , 11 In vitro analysis has shown that this variant retains 24% to 28% residual PPA2 activity. 2 Of the 14 individuals reported with this variant, 4 died in infancy, 5 died following alcohol consumption, and 5 are currently living with hypersensitivity to alcohol ( Table 2 ).…”
Section: Investigationsmentioning
confidence: 99%
“… 2 Of the 14 individuals reported with this variant, 4 died in infancy, 5 died following alcohol consumption, and 5 are currently living with hypersensitivity to alcohol ( Table 2 ). 2 , 7 , 8 , 9 Three living individuals have myocardial fibrosis, and 1 has a purely neurologic presentation of progressive cerebellar ataxia. 7 The maternally inherited variant, c.987 G>A (p.W329∗), is a novel nonsense sequence variant resulting in truncation of the last 6 amino acids of the PPA2 protein.…”
Section: Investigationsmentioning
confidence: 99%
See 2 more Smart Citations